Breadth of Functional Antibodies Is Associated With Plasmodium falciparum Merozoite Phagocytosis and Protection Against Febrile Malaria. (1st March 2019) - Kana, Ikhlaq Hussain; Singh, Susheel Kumar; Garcia-Senosiain, Asier; Dodoo, Daniel; Singh, Subhash; Adu, Bright; Theisen, Michael
Abstract: Background: The specific targets of functional antibodies against Plasmodium falciparum merozoites remain largely unexplored and, more importantly, their relevance to naturally acquired immunity in longitudinal cohort studies (LCSs) is yet to be tested. Methods: Functionality of immunoglobulin G (IgG) antibodies against 24 merozoite antigens was determined at the baseline of an LCS in Ghana using a bead-based opsonic phagocytosis assay (BPA). Antigen-specific IgG3 subclass antibodies were quantified in the same samples by the Luminex multiplex system. Results: A wide range of BPA activity was observed across the different antigens. High BPA responses of nMSP3 K1, GLURP-R2, MSP2 3D7, MSP119k, and PfRh2-2030 coupled beads were significantly associated with a higher probability of children not experiencing febrile malaria. Children with high breadth of functional antibodies against these antigens together with cMSP3 3D7 had a significantly reduced risk of febrile malaria (adjusted hazard ratio, 0.36 [95% confidence interval, .18–.72]; P = .004). Five of the 6 BPA activities significantly (likelihood ratio rest, P ≤ .05) contributed to the protective immunity observed with the IgG3 antibodies. Conclusions: The development of BPA allowed profiling of functional antibodies in an LCS. Identification of targets of opsonic phagocytosis may have implications in the development of a subunit malaria vaccine. Abstract : Using a bead-based bioassay, we identified 6 (nMSP3 K1, GLURP-R2, MSP2 3D7, MSP119k, PfRh2-2030, and cMSP3 3D7 ) Plasmodium falciparum merozoite antigens as targets of functional antibodies that confer protection against febrile malaria in a cohort of Ghanaian children.